2010
DOI: 10.1503/cmaj.100511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of death and dying on the personal lives and practices of palliative and hospice care professionals

Abstract: A lthough preserving life is a central goal of medicine, in the end, death is an unavoidable outcome. Professionals in palliative and hospice care, working within the landscape of death and dying, are able to provide insight into death-related experiences and have the opportunity to incorporate these ex periences into their personal and professional lives. The ability for death to foster meaning in life has been attested to by wisdom traditions and palliative care professionals alike. The latter usually provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 28 publications
8
97
0
6
Order By: Relevance
“…They believed facing one's mortality to be helpful and possibly a requirement to providing effective care to the dying. This study showed life-affirming lessons learned by clinicians from those who are nearing death (Sinclair, 2011). …”
Section: Existential Theory and Palliative Carementioning
confidence: 62%
See 1 more Smart Citation
“…They believed facing one's mortality to be helpful and possibly a requirement to providing effective care to the dying. This study showed life-affirming lessons learned by clinicians from those who are nearing death (Sinclair, 2011). …”
Section: Existential Theory and Palliative Carementioning
confidence: 62%
“…Sinclair's (2011) ethnographic inquiry sought to produce detailed understanding of the impact of death and dying on 24 clinicians who provided end-of-life care. Analysis of semi-structured interviews and participant observation discovered three overarching categories (e.g., past, present, future) and 11 themes from the data.…”
Section: Existential Theory and Palliative Carementioning
confidence: 99%
“…For instance, we documented the emotional work required in attempting to support people with cancer and their families Kovács et al, 2010) and the protective role of self-care strategies for professionals engaging in this work (Kearney, Weininger, Vachon, Harrison, & Mount, 2009;Trufelli et al, 2008). Additionally, we emphasize the need for workplace, as well as individual, strategies that acknowledge the health professionals' feelings and needs and bolster their communication skills Pereira et al, 2011;Trufelli et al, 2008), as well as highlighting the job satisfaction that often accompanies such roles (Ablett & Jones, 2007;Sinclair, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Em alguns casos, a experiência profissional é considerada como uma aliada para lidar com as situações adversas e imprevisíveis que incluem o evento da morte, facilitando a sua aceitação, ou seja, ela pode contribuir para que algumas pessoas adquiram esperança, compaixão, apurem o autoconhecimento, tornando-se mais sensíveis e preparadas para o enfrentamento da morte (15)(16) . Contudo, a subjetividade inerente ao ser humano não iguala as formas de pensamento, nem tão pouco, iguala os modos de cada profissional lidar com esse acontecimento em seu cotidiano de trabalho (13) .…”
Section: Cuidado De Si Adotado Por Enfermeiros Frente à Possibilidadeunclassified